Informational Support of Cash Flow Management Processes in Public Administration - Husiatynskyi, Mykola Volodymyrovych (International Journal of Innovative Technology and Exploring Engineering, 2019)
Management functions of the state in the field of regulation of financial flows is the basis of a modern market economy. The intricate and complex nature of the control object itself also forces us to continually look for ways to increase the effectiveness of both analysis and planning techniques. High-quality informational support predetermines the effectiveness of managerial decisions in the sphere of regulation of financial flows. The wide variability of information support is the key to the ability to apply effectively administrative impact. At the same time, accounting, control and analysis are interconnected management functions that provide information support for making management decisions at any level. The information analysis technique based on fuzzy decision trees is an innovative and well-proven way to provide government institutions with a reliable analytical tool.

Управлінські функції держави в галузі регулювання фінансових потоків є основою сучасної ринкової економіки. Складний і складний характер самого об'єкта управління також змушує нас постійно шукати шляхи підвищення ефективності як методів аналізу, так і планування. Якісна інформаційна підтримка зумовлює ефективність управлінських рішень у сфері регулювання фінансових потоків. Широка варіативність інформаційної підтримки є запорукою здатності ефективно застосовувати адміністративний вплив. Водночас облік, контроль та аналіз - це взаємопов’язані функції управління, які забезпечують інформаційну підтримку для прийняття управлінських рішень на будь-якому рівні. Метод аналізу інформації, заснований на нечітких деревах рішень, є інноваційним і добре перевіреним способом забезпечити державні установи надійним аналітичним інструментом.
Keywords: грошовий потік, інформаційна підтримка, управління, державне управління; cash flow, informational support, management, public administration